2016
DOI: 10.20471/acc.2016.55.04.19
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Ruptured Middle Cerebral Artery Aneurysm Followed by Subarachnoid Hemorrhage and Acute Subdural Hematoma in Multiple Aneurysm Disease of Cerebral Blood Vessels: Case Report

Abstract: SUMMARY -Aneurysms of blood vessels at the base of the brain are pathological focal outpouchings, usually found at the branching points of the arteries. Aneurysm can remain silent for life. Clinical presentation is due to rupture and bleeding. In only 1.3% of cases it results in subdural hematoma, which is associated with direct interaction of the aneurysm with the basal arachnoid membrane. Multiple aneurysms are present in 15% to 33% of cases with subarachnoid hemorrhage. Assessment of these patients is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although the prognosis of neurosarcoidosis is good, particularly when facial nerve is involved, hydrocephalus is associated with a high mortality rate of 75% 12,13 . Benzagmout et al report that after treatment with ven tricular shunt and corticosteroid therapy, acute hydrocephalus associated with neurosarcoidosis was resolved 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prognosis of neurosarcoidosis is good, particularly when facial nerve is involved, hydrocephalus is associated with a high mortality rate of 75% 12,13 . Benzagmout et al report that after treatment with ven tricular shunt and corticosteroid therapy, acute hydrocephalus associated with neurosarcoidosis was resolved 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Benzagmout et al . report that after treatment with ventricular shunt and corticosteroid therapy, acute hydrocephalus associated with neurosarcoidosis was resolved ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report described a 44-yearold woman with multiple cerebral aneurysm disease who was urgently treated after rupture by simultaneous endovascular and surgical approaches under general anesthesia, resulting in complete recovery of the patient. 22 Patients often develop significant cognitive impairment early after acute ICH; this is more frequent in patients of advanced age, female patients, and patients with prior acute ICH. 23 The present study showed that neurological impairment is associated with 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%